A randomised comparison of free‐handed vs air‐Q™ assisted fibreoptic‐guided tracheal intubation in children < 2 years of age1. (2nd May 2014) - Sohn, L. E.; Jagannathan, N.; Sequera‐Ramos, L.; Sawardekar, A.; Schaldenbrand, K.; De Oliveira, G. S.
Summary We prospectively compared free‐handed and air‐Q™ assisted fibreoptic‐guided tracheal intubation in children < 2 years of age. Eighty healthy children were enrolled and randomly assigned to a technique (free‐handed or air‐Q assisted) and operator (trainee or attending). Time, number of attempts and manoeuvres required were assessed. There was no difference in median (IQR [range]) time to successful tracheal intubation between the free‐handed (52.2 (34.8–67.7 [19.7–108.0]) s), and the air‐Q assisted (60.3 (45.5–75.1 [28.1–129.0]) s; p = 0.13) groups, or the number of attempts needed. The air‐Q assisted group required fewer manoeuvres to optimise the laryngeal view (median (IQR [range]) 0 (0–1 [0–2])) than the free‐handed group (1 (1–1 [0–3]); p < 0.001). In conclusion, fibreoptic‐guided tracheal intubation times were similar with and without the use of the air‐Q, but supraglottic airway devices may be a consideration for their other practical advantages.